PRODUÇÃO E USO DAS VIDEOAULAS EM ESCOLAS PÚBLICAS DO ENSINO FUNDAMENTAL: PERSPECTIVA DE DOCENTES DO GÊNERO FEMININO E MASCULINO - LEANDRO PICCINI BARBOSA (2023)
This master's research is linked to the Graduate Program in Education (PPGEdu) of the Faculty of Education (FAED), of the Federal University of Mato Grosso do Sul (UFMS) in the three research lines: Training Processes, Educational Practices, Differences. Its objective is to identify the opinions and the challenges experienced by teachers, from Rede Municipal de Ensino de Campo Grande - MS, to produce and use video classrooms in teaching activities. With the aim of obtaining diverse scientific views, it was established as the beginning of its methodological course or inventory and study of existing scientific productions that would privilege in its investigations the interlocution of two topics that integrate this work. Then, the field research began, with teachers who produce or make use of video classrooms in their practices and, who attained the final years of the fundamental education of the Municipal Education Network of Campo Grande - MS. The first stage of the empirical research was carried out by means of an online form, which was answered by 22 teachers. The second stage, of a qualitative nature, occurred through the recording of interviews with 5 teachers and 3 teachers from the capital Campo Grande. The results show that there are many challenges experienced by teachers, mainly in relation to the technological domain, appropriate methodologies for the production of video classrooms and in relation to the work routine during the period of emergency remote teaching. These are different challenges for men and women, mainly women with children, who may need to dedicate themselves to meeting their personal and educational work demands in the pandemic context. Likewise, it is suggested that new research on the use of video classrooms be carried out, so technological resources should not be ignored and the return of an education prior to the Internet era should not be ignored. On the contrary, it is necessary to study, deepen and provide critical ways to appropriate the tools and carry out an educational work with mastery. Not that tange as questions of gender, nothing would advance the school to direct a teacher who lives with the children to produce video classroom, since her physical space does not allow her to carry out this activity at home. Logo, it is suggested that spaces and technological resources be available in the school itself, for the production of video classrooms, contributing as well as the teachers who are interested in using this pedagogical resource, regardless of whether these teachers are male or female.